(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Management of progressive myopia is a major issue in current optometry and oph-thalmology in general. Refractive therapy with orthokeratology lenses (OKL) has become an in-creasingly popular technique for controlling the progression of myopia. Purpose: To assess the efficacy of orthokeratology lenses depending on the topography pupil size and lens optical zone (OZ) size. Material and Methods: Sixty children (117 eyes) with mild or moderate uncomplicated myopia were involved in this study. They underwent a comprehensive eye examination, corneal topography and pupillometry. Statistical analysis of correlations between the pupil diameter and axial elongation was performed. In order to conduct longitudinal surveillance of myopia, we compared two OKL designs, one with a conventional OZ diameter, and another with a smaller OZ diameter, for the efficacy of myopia control. Results: The pupil diameter was inversely correlated with the axial elongation both in mild myopes (r = -0.48, p < 0.001) and in moderate myopes (r = -0.7, p < 0.001). Patients showed slower axial length progression when treated with a 5.5-mm OZ lens design than with a conventional 6.0-mm OZ lens design. Conclusion: When examining a child with progressive myopia, it is important to pay attention to the photopic pupil size because the size may be a predictor of myopia progression and exert an influ-ence on the choice of correction. Orthokeratology lenses with a smaller (5.5-mm) optical zone diam-eter are more effective for myopia control, which should be taken into consideration when selecting a lens design for children.